The Influence of Air Pollution on Accounting Conservatism (Empirical Study of Manufacturing Companies in Indonesia) - Ma'sum, Muhammad Ali; Sunarto, Sunarto; Hardiningsih, Pancawati (Jurnal Akuntansi dan Perpajakan, 2024)
Air pollution is an important factor that influences the risk perception of stakeholders including investors and managers. Managers' risk perception is a factor that determines accounting conservatism and reporting strategies. This study examines whether in response to the risk of increasing air pollution, companies implement more conservative accounting policies. In addition, this study also tests whether conservative accounting policies in response to the risk of increasing air pollution will be more prominent in companies under high financial constraints. Using a sample of manufacturing companies in Indonesia and air quality index (IKU) issued by the Ministry of the Environment and tested with panel data regression, this study shows that companies implement more conservative accounting policies as response to the risk of increasing air pollution. However, the accounting conservatism policy was not proven to be more prominent in companies under high financial constraints.Â